2022
DOI: 10.1038/s41419-022-05112-0
|View full text |Cite
|
Sign up to set email alerts
|

XAF1 drives apoptotic switch of endoplasmic reticulum stress response through destabilization of GRP78 and CHIP

Abstract: X-linked inhibitor of apoptosis-associated factor-1 (XAF1) is a stress-inducible tumor suppressor that is commonly inactivated in many human cancers. Despite accumulating evidence for the pro-apoptotic role for XAF1 under various stressful conditions, its involvement in endoplasmic reticulum (ER) stress response remains undefined. Here, we report that XAF1 increases cell sensitivity to ER stress and acts as a molecular switch in unfolded protein response (UPR)-mediated cell-fate decisions favoring apoptosis ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…3c ). In XAF1 that is known to be transcriptionally activated by oxidative stress 38 , we found oxidation of Cys112 upon IFN stimulation. As expected, the IFN-α treatment led to changes in the REXpression and solubility of many known and putative ISGs ( Fig.…”
Section: Resultsmentioning
confidence: 72%
“…3c ). In XAF1 that is known to be transcriptionally activated by oxidative stress 38 , we found oxidation of Cys112 upon IFN stimulation. As expected, the IFN-α treatment led to changes in the REXpression and solubility of many known and putative ISGs ( Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Interestingly, its expression has been relevant in the pathogenesis of BC due to its role in motility, invasion, metastasis, and a poor response to chemotherapy and radiotherapy 138 , 139 . Additionally, XAF1 counteracts the inhibitory effect of apoptosis (13 degrees) 140 , IFIT2 involve positive regulation of the apoptotic process and response to the virus (13 degrees) 141 , RSAD2 is an interferon-inducible antiviral protein (13 degrees), and OAS2 involved in the innate immune response to viral infection (13 degrees) 142 . The Basal B network consists of 40 nodes and 28 edges.…”
Section: Resultsmentioning
confidence: 99%
“…These interactions make it suitable for XAF1 to function as a VCP adaptor protein to regulate the deubiquitination and stability of RNF114. It is reported that XAF1 interacts with ER stress sensor glucose-regulated protein (GRP78) via the C-terminal region, leading to the degradation of GRP78 in an RNF114-dependent manner ( Lee et al, 2022 ). XAF1 interacts with ERα and BRCA1 via the ZF domains 5/6 and 4, respectively, and destabilizes ERα through the assembly of BRCA1-mediated destruction complex and promotes estrogen-induced apoptosis ( Lim et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%